Experimental study on single phase flow characteristics in tight sandstone oil reservoirs. Issue 4 (April 2020) - Liu, X F; Zhao, Z L; Li, J F; Sun, N; Chen, Z J; Ji, A Z
Abstract: Tight oil resource is distributed worldwide and has great potential for exploration. As tight sandstone reservoirs have small pores and narrow throats, the liquid boundary layer has great influence on the seepage, inducing starting pressure gradient during fluid seepage. In this paper, flow characters of both single water and single oil phase is investigated. Results show that the curve of flow velocity vs. the pressure difference doesn't pass through the origin. Extending the trend line will intersect the abscissa pressure difference, indicating it is non-Darcy flow for both single water and oil in tight sandstone cores. The permeability increases slowly with the increase of displacement pressure difference until basically stable.